2008
DOI: 10.1086/589500
|View full text |Cite
|
Sign up to set email alerts
|

The Milky Way’s Circular Velocity Curve to 60 kpc and an Estimate of the Dark Matter Halo Mass from the Kinematics of ∼2400 SDSS Blue Horizontal‐Branch Stars

Abstract: We derive new constraints on the mass of the Milky Way's dark matter halo, based on a set of halo stars from SDSS as kinematic tracers. Our sample comprises 2401 rigorously selected Blue Horizontal-Branch (BHB) halo stars at |z| ≥ 4 kpc, and with distances from the Galactic center up to ∼ 60 kpc, with photometry and spectra drawn from SDSS DR-6. With distances accurate to ∼ 10%,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

47
520
2
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 628 publications
(574 citation statements)
references
References 64 publications
47
520
2
5
Order By: Relevance
“…In this case, the fact that the MW has only three satellites with V max ≥ 30 km s −1 (the two MCs and Sagittarius) requires the virial mass of the MW halo to be M 200 < 1.4 × 10 12 M at 90 per cent confidence; on the other hand, the existence of the two MCs, which have V max ≥ 60 km s −1 , requires M 200 > 1.0 × 10 12 M , also at 90 per cent confidence. This conclusion is consistent with some, but not all, recent measurements of the MW mass (Battaglia et al 2005;Smith et al 2007;Xue et al 2008;Guo et al 2010;Watkins, Evans & An 2010;Busha et al 2011a;González, Kravtsov & Gnedin 2014;Diaz et al 2014;Piffl et al 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this case, the fact that the MW has only three satellites with V max ≥ 30 km s −1 (the two MCs and Sagittarius) requires the virial mass of the MW halo to be M 200 < 1.4 × 10 12 M at 90 per cent confidence; on the other hand, the existence of the two MCs, which have V max ≥ 60 km s −1 , requires M 200 > 1.0 × 10 12 M , also at 90 per cent confidence. This conclusion is consistent with some, but not all, recent measurements of the MW mass (Battaglia et al 2005;Smith et al 2007;Xue et al 2008;Guo et al 2010;Watkins, Evans & An 2010;Busha et al 2011a;González, Kravtsov & Gnedin 2014;Diaz et al 2014;Piffl et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…We take haloes in the mass range (0.8-3) × 10 12 M as reference since this interval encompasses the likely value for the MW as seen in the preceding section and also as argued by e.g. Battaglia et al (2005), Dehnen, McLaughlin & Sachania (2006), Xue et al (2008), Gnedin et al (2010), Guo et al (2010). The figure shows that, to (10-20) per cent accuracy, the number of substructures is independent of host halo mass over the mass range 10 11 -10 13 M .…”
Section: T H E M a S S D I S T R I B U T I O N O F T H E M Wmentioning
confidence: 99%
“…Although the halo mass of Milky Way itself is in debate (e.g. Xue et al (2008) and references therein), we take a relatively lower mass among suggested values. For a (slightly) small value of M halo , the relative mass ratio M satellite /M halo becomes larger.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…For regions beyond the Galactic disc, the RC needs to be measured using halo stars, such as the blue horizontal branch (BHB) stars (Xue et al 2008;Deason et al 2012;Kafle et al 2012;Williams & Evans 2015) and the K giants (Bhattacharjee, Chaudhury, & Kundu 2014, hereafter BCK14), globular clusters or dwarf galaxies. For those tracers of halo populations (assuming isotropically distributed), the radial velocity dispersion σr, number density ν and velocity anisotropy parameter β ≡ 1 − σ 2 t /σ 2 r , are linked to the circular velocity Vc through the Jeans equation (see, e.g.…”
mentioning
confidence: 99%
“…BCK14) or predicted by numerical simulations (e.g. Xue et al 2008;BCK14) have been adopted in the spherical Jeans equation to derive the RC. Only more recently, some constraints on the anisotropy parameter, mainly for the inner halo ( 25 kpc), have become available, based on some direct/indirect measurements (e.g.…”
mentioning
confidence: 99%